Solid state physics : - Wahab, M A (Alpha Science International, 2005)
This book presents a comprehensive study of various topics of solid state physics for the undergraduate and postgraduate students of pure and applied sciences, and engineering disciplines. The text is divided into eighteen chapters. First seven chapters deal with structure related aspects such as lattice and crystal structures, bonding, packing and diffusion of atoms followed by imperfections and lattice vibrations. Chapter eight deals mainly with experimental methods of determining structures of given materials. The next nine chapters cover various physical properties of crystalline solids